Influencia del aislamiento social en el estado de salud físico y emocional de los pacientes del asilo Virgen del Carmen del Cantón Chambo julio a diciembre del 2013. - Morocho Tenesaca, Gladys Susana (2013)
The research topic is "Quality of life of stoma patients , graduates of the surgery of the Provincial General Hospital Faculty of Riobamba and its relationship to nursing care in the period January to June 2013 ," the same was done with the purpose of determining the quality of life of stoma patients and thus seek a solution to the problem identified . For this non experimental research descriptive field was proposed. The sample consists of 13 licensed nurses who work in the department of surgery, one licensed nurse working in outpatient Riobamba General Teaching Hospital and 15 ostomy patients graduates from January to June 2013. The data collection was performed by applying a survey of professional nursing staff with the use of an observation guide , the survey aimed at Montreux ostomy patients graduates are also conducted to measure the quality of life of same .